2022
DOI: 10.3390/pr10102022
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Hydraulic Fracturing in Ductile Reservoirs: Theory, Simulation, and Experiment

Abstract: The bottom-hole pressure of hydraulic fracturing in ductile reservoirs is much higher than that of the hydraulic fracturing simulation, and the fracture toughness inferred from the field data is 1–3 orders of magnitude higher than that measured in the laboratory. The rock apparent fracture toughness increases with the increase in the confining pressure. Excluding the influence of the fluid viscosity and the fluid lag on the apparent fracture toughness, the fracture process zone (FPZ) at the fracture tip can ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 228 publications
0
3
0
Order By: Relevance
“…Generally, both mechanical properties are increased at such conditions compared to the reference condition (i.e., stress‐free laboratory conditions with no confining pressure). For example, Zhu et al, 75 Thiercelin 76 and Zhao and Roegiers 40 presented the fracture toughness ( K Ic ) versus the confining pressure data for different rocks, including limestone, sandstone, tuff, mudstone, shale, and basalt and showed that the fracture toughness increases almost linearly by increasing the confining pressure but the slope of changes for the K Ic value significantly depends on the rock type. Also, according to their study, the fracture toughness of rocks can be increased up to 5 times when the confining pressure value varies from zero to about 60 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, both mechanical properties are increased at such conditions compared to the reference condition (i.e., stress‐free laboratory conditions with no confining pressure). For example, Zhu et al, 75 Thiercelin 76 and Zhao and Roegiers 40 presented the fracture toughness ( K Ic ) versus the confining pressure data for different rocks, including limestone, sandstone, tuff, mudstone, shale, and basalt and showed that the fracture toughness increases almost linearly by increasing the confining pressure but the slope of changes for the K Ic value significantly depends on the rock type. Also, according to their study, the fracture toughness of rocks can be increased up to 5 times when the confining pressure value varies from zero to about 60 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…The size bottleneck of experimental specimens remains an intractable problem. 22,23 The rapid development of numerical methods and computer technology provides an effective way to study hydraulic fracture propagation in large-scale low-permeability reservoirs and compensates for the shortcomings of experimental research. 24−26 In recent years, many researchers have employed numerical methods to create large-scale three-dimensional (3D) fracturing models to study the behavior of fracture propagation during multiple horizontal well fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many problems are difficult to study in the laboratory, such as the reservoir with stratum property difference fracturing, multi-well fracture propagation, and interactions among wells. The size bottleneck of experimental specimens remains an intractable problem. , …”
Section: Introductionmentioning
confidence: 99%